Large Amoebic Liver Abscess with Persistent Biliary Fistula - Shah, Apurva S.; Bohra, Shravan (Journal of Digestive Endoscopy, 2018)
Liver abscess with biliary communication poses management problem if percutaneous drainage is performed. We report a case of large amoebic liver abscess (ALA) with jaundice. Prolonged high‑output bile drainage after percutaneous drainage of ALA showed suspicion of communication of abscess with intrahepatic bile ducts (biliary fistula). The same was managed successfully with endoscopic biliary stent placement with medical management.
Keywords: Amebic liver abscess; biliary fistula; biliary stent